Authority Of Local Governments In Issuing Environmental Impact Assessment Permits - Rahadyan Widarsadhika Wisnumurti (Fakultas Hukum Dehasen, 2024)
This study aims This study seeks to reassess the jurisdiction of local governments in granting Environmental Impact Assessment (AMDAL) permits in light of legal amendments, specifically Law Number 6 of 2023 regarding the Ratification of Government Regulation replacing Law Number 2 of 2022 on Job Creation. The Indonesian government has enacted a policy of regional autonomy to delegate greater authority to local governments in managing affairs within their regions. Environmental management is a key focus of regional autonomy implementation. Effective environmental management is essential for ensuring sustainable development in Indonesia, which boasts plentiful natural resources. Law Number 32 of 2009 on Environmental Protection and Management provides the regulatory foundation for matters related to industrial elements, law enforcement, and community involvement. This research aims to enhance understanding of the effects of regulatory changes on regional autonomy in environmental management and to provide policy recommendations for maintaining the balance between environmental sustainability and local government empowerment.